Evolutionary history of adenomas to colorectal cancer in FAP families - Yang, Cuiping; Xiang, Enfei; Chen, Ping; Fang, Xuqian (Frontiers in Genetics, 2024)
Objective Familial adenomatous polyposis (FAP) is a genetic syndrome characterized by multiple polyps at various evolutionary stages, which, if left untreated, inevitably progress to colorectal cancer (CRC). In this study, we present a comprehensive analysis of the evolutionary history of FAP-CRC from precancerous adenoma to carcinoma. Design Tissues were collected from gastrointestinal endoscopy or surgical resection . Exome sequencing was performed on multiple regions of adenocarcinoma (n = 8), villous adenoma (n = 10), tubular adenoma (n = 9) and blood samples were obtained from 9 patients belonging to 7 Chinese FAP families. Phylogenetic trees were reconstructed, and evolutionary analysis was conducted to reveal the temporal sequence of events leading to CRC. Results Inherited germline mutation sites in APC gene were identified in FAP01 (p.S1281*, COSM19212), FAP03 (p.S384Tfs*19), FAP04 (p.E1538*, COSM6041693), FAP05 (p.Q1062*, COSM3696862), and FAP07-FAP09 (p.V677Sfs*3). Notably, p.V677Sfs*3 mutation was recognized as a novel germline mutation in APC, supported by evidence of genotype-phenotype correlation in pedigree analysis. Adenomas exhibited lower mutational rates than FAP-CRC and displayed recurrent alterations in well-known chromosomal instability (CIN) genes (APC, RAS, SMAD4 and TP53) and DNA damage repair genes (SUZ12, KMT2C, BCLAF1, RUNX1, and ARID1B), suggesting the presence of genomic instability. Furthermore, a progressive increase in the HRD score (a measure of "genomic scars") was observed from tubular adenomas to villous adenomas and ultimately to carcinomas. TP53 emerged as the primary driver gene for adenoma-carcinoma transition, with driver mutations consistently appearing simultaneously rather than sequentially acquired from adenomas to carcinomas. Clonal evolution demonstrated that liver metastases can originate from the same cancer-primed cell present in a primary cancerous lesion. Conclusion We identified a novel pathogenic variant in APC, namely p.V677Sfs*3.The process of carcinogenesis in FAP-CRC supports the classical cancerization model, where an initial APC mutation leads to the activation of the WNT signaling pathway and CIN. Subsequently, additional mutations occur in other putative CIN genes (e.g. DNA repair, chromatin remodeling), ultimately leading to the development of microsatellite-stable (MSS) tumors. Our study provides a comprehensive understanding of the genomic landscapes that underlie the transition from adenoma to carcinoma.